THE LAW EDUCATION AND MAKING THE BIRTH CERTIFICATE AS PROTECTION FORM FOR THE CHILDREN - Marlina; Mahmud Mulyadi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The birth of a child is a gift and the happiness of parents. The birth is an important event in population administration. Each child must get clear and correct self identity. Birth certificate is an identity form of a child that needs to do by parents as a protection form for the child. The parents’ understanding about birth certificate is still lacking especially in partner village. The condition creates an idea to do a law education and accompaniment to make birth certificate with involves the role of village official, provision districts and related agencies. The used method is delivered the material by tutorial lecture to the society by bringing Department of population and civil registration in making birth certificate by involving village official, provision districts and society to find the policy form to protect child with clear and correct self identity. The next stage is accompaniment in making birth certificate and cooperation all materials to the ownership of child as a protection for the children. The result of service shows creating an understanding of partner society in the ownership of birth certificate and the protection form of the child status and the marriage status, and the fulfillment of other requirement in making certificate as the guide book. The result of accompaniment and cooperation in Department of population and civil registration succeed to publish 61 marriage certificate from 67 couples which presents with 2 witnesses when notes in Department of population and civil registration from 123 application marriage certificate submitted. Next form the marriage certificate submitted to publish of birth certificate. The birth certificate which succeeds to be published 107 birth certificate from 162 application birth certificate submitted by society. The failure of submitted certificate because the lack of data, lack of requirement, the discrepancy data, and published the birth certificate.